Brown eye spot incidence in fruits of coffee: different density planting and water managements - Vasco, Gabriel Brandão; Pozza, Edson Ampélio; Scalco, Myriane Stella; Santos, Leone Stabile Dias; Custódio, Adriano Augusto de Paiva; Silva, Mirian de Lourdes Oliveira e (Coffee Science - ISSN 1984-3909, 2015)
The objective of this study was to evaluate the incidence of cercospora leaf spot, on coffee plant fruits, under different irrigation management and planting densities. The trial was carried out at the Federal University of Lavras in the agricultural year 2008/2009 and 2009/2010, and collected 320 fruits per plot. The experimental design was a randomized block with four replicates. The treatments correspond to the densities of 2,500, 3,333, 5,000 and 10,000 plants ha-1 and six subplots: control (T0), irrigation throughout the year when the soil water tension reached values of 20 and 60 kPa (T1 and T2), irrigation when water tension reached values of 20 kPa and 60 kPa and suspended during the months of July and August or when the water deficit was more than 100 mm (T3 and T4) and saw irrigation using software Irriplus (T5). The highest incidence of gray leaf spot, in Lavras/MG depends on the rainfall and rainfall distribution of the agricultural year. There was a significant interaction between irrigation management and planting density, only in the 2010 harvest. In the 2009 harvest, the interaction between irrigation and plant density was not significant due to good rainfall during this period. There was a higher incidence of the disease, on the densities of 3,333 (19.58%) and 5,000 (18.06%) plants ha-1. In the 2010, higher incidence (35.50%) of the disease in control (T0), and the lower incidence in treatments T4 (8.31%) and T5 (12.80%), on the density of 2.500 plants.ha -1.